Crisis management at South African universities: A case of the University of Cape Town crisis management strategies - Makubalo, Siyavuya (Centre for Film and Media Studies, 2024)
In recent years, crises have become frequent in society, affecting individuals, organisations, and institutions. Traditionally, higher education institutions were regarded as protected spaces. However, with the rising cost of tuition that significantly affects students from less privileged backgrounds, higher education institutions have been facing increasing crises in the form of student protests. When these crises have emerged, higher education institutions have resorted to implementing crisis response plans rather than developing crisis prevention strategies. The former can be distinguished from the latter by its focus on short-term resolution, which allows for crisis dormancy. This study examines whether higher education institutions' failure to distinguish between dormant and resolved crises has contributed to a culture of crisis management rather than crisis prevention.